Detection of Structural Variations and Fusion Genes in Breast Cancer Samples Using Third-Generation Sequencing - Hu, Taobo; Li, Jingjing; Long, Mengping; Wu, Jinbo; Zhang, Zhen; Xie, Fei; Zhao, Jin; Yang, Houpu; Song, Qianqian; Lian, Sheng; Shi, Jiandong; Guo, Xueyu; et al. (Frontiers in Cell and Developmental Biology, 2022)
Background: Structural variations (SVs) are common genetic alterations in the human genome that could cause different phenotypes and various diseases including cancer. However, the detection of structural variations using the second-generation sequencing was limited by its short read-length which in turn restrained our understanding of structural variations. Methods: In this study, we developed a 28-gene panel for long-read sequencing and employed it to both Oxford Nanopore Technologies and Pacific Biosciences platforms. We analyzed structural variations in the 28 breast cancer-related genes through long-read genomic and transcriptomic sequencing of tumor, para-tumor and blood samples in 19 breast cancer patients. Results: Our results showed that some somatic SVs were recurring among the selected genes, though the majority of them occurred in the non-exonic region. We found evidence supporting the existence of hotspot regions for SVs, which extended our previous understanding that they exist only for single nucleotide variations. Conclusions: In conclusion, we employed long-read genomic and transcriptomic sequencing in identifying SVs from breast cancer patients and proved that this approach holds great potential in clinical application.